An innovation developing flip flop book (digital) on organ systems in human - N Sartono; M Suprapto; I J Ichsan (Pascasarjana Universitas Pendidikan Indonesia, 2018)
New trend in education leads to computer-based education, a variety of multimedia-based learning resources such as flip flop book. Flip flop book provides a combination of text, images, animations, and videos in one application. Thus students can learn optimally. The research aim is measuring effectiveness flip flop book to learning outcomes. The material chosen in the development of the flip flop book in this study is the material of the Organ Systems in Human. This material is selected based on need assessment which shows that some of the material on Human Organ System is the most difficult material in class XI. The research method used is Research and Development with Borg and Gall model, 2007. The research held in Senior High School . In learning the use of flip flop book is expected to improve student learning outcomes. From the results of the feasibility study by experts, small group trials, and large groups (whole class) show the results of Good (B) to Very Good (SB) indicator, from the value of 76 to 85 for the feasibility test. The effectiveness test results show a value of p <.05, which means that classes using digital books are better than that do not use. Conclusion that the development of digital books (Flip Flop Book) has a rating good to very good.